Investasi Etis Di Kalangan Institusi Katolik Di Indonesia - Yohanes I Wayan Marianta; Valentinus Saeng (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study explores ethical investment practices among Catholic institutions in Indonesia. As a relatively rare area of inquiry, the research investigates the extent to which Catholic institutions have sought to translate the principles of Catholic Social Teaching (CST) into the field of investment. Data were collected through interviews with key participants from three dioceses and six congregations. The findings reveal that these institutions have endeavored to implement ethical principles derived from CST. Due to limitations in their capacity to conduct screening and analysis of various investment options, they have adopted a strategic approach by utilizing the services of an investment consultancy team from the Indonesian Bishops’ Conference (KWI). Drawing on Max Weber’s theoretical framework, this practice is interpreted as a form of social action grounded in “value-rationality.” Thus, investment activities pursued rationally for financial gain are framed within the values of CST. In this way, Catholic institutions have sought to establish faith-based ethical investment practices.